2022
DOI: 10.1155/2022/2121463
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Value of CBL‐Based Teaching Mode in Training Medical Students’ Achievement Rate, Practical Ability, and Psychological Quality

Abstract: In order to improve the quality of medical student training, the clinical case-based learning (CBL) teaching mode is analyzed in the aspect of the rate of achievement, practical ability, and psychological effect. A total of 86 medical students who came to our hospital from March 2020 to December 2021 are selected and divided into the CBL group and the control group according to the random number table method. The psychological quality of medical students is evaluated by observing their movements and expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Đánh giá tâm lý bao gồm quan sát cử động và bộ câu hỏi đánh giá điểm số về hoạch định tương lai, sức khỏe nghề nghiệp và tinh thần tập thể. Kết quả cho thấy ảnh hưởng tích cực của phương pháp giảng dạy CBL đối với sự phát triển và tự tin của sinh viên y khoa [17].…”
Section: Các Nghiên Cứu đáNh Giá Giáng Dạy Theo Cbl Trong Khối Ngành ...unclassified
“…Đánh giá tâm lý bao gồm quan sát cử động và bộ câu hỏi đánh giá điểm số về hoạch định tương lai, sức khỏe nghề nghiệp và tinh thần tập thể. Kết quả cho thấy ảnh hưởng tích cực của phương pháp giảng dạy CBL đối với sự phát triển và tự tin của sinh viên y khoa [17].…”
Section: Các Nghiên Cứu đáNh Giá Giáng Dạy Theo Cbl Trong Khối Ngành ...unclassified
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%